A Class of p-Valent Meromorphic Functions Defined by the Liu–Srivastava Operator - Seoudy, T. M. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We introduce a subclass of p-valent meromorphic functions involving the Lui–Srivastava operator and investigate various properties of this subclass. We also indicate the relationships between various results presented in the paper and the results obtained in earlier works.